Cervical Dystonia: A Disorder of the Midbrain Network for Covert Attentional Orienting - Hutchinson, Michael; Isa, Tadashi; Molloy, Anna; Kimmich, Okka; Williams, Laura; Molloy, Fiona; Moore, Helena; Healy, Daniel G.; Lynch, Tim; Walsh, Cathal; Butler, John; Reilly, Richard B.; et al. (Frontiers in Neurology, 2014)
While the pathogenesis of cervical dystonia remains unknown, recent animal and clinical experimental studies have indicated its probable mechanisms. Abnormal temporal discrimination is a mediational endophenotype of cervical dystonia and informs new concepts of disease pathogenesis. Our hypothesis is that both abnormal temporal discrimination and cervical dystonia are due to a disorder of the midbrain network for covert attentional orienting caused by reduced gamma-aminobutyric acid inhibition, resulting from, in turn, from as yet undetermined, genetic mutations. Such disinhibition is a) subclinically manifested by abnormal temporal discrimination due to prolonged duration firing of the visual sensory neurons in the superficial laminae of the superior colliculus, b) clinically manifested by cervical dystonia due to disinhibited burst activity of the cephalomotor neurons of the intermediate and deep laminae of the superior colliculus. Abnormal temporal discrimination in unaffected first-degree relatives of patients with cervical dystonia represents a subclinical manifestation of defective gamma-aminobutyric acid activity both within the superior colliculus and from the substantia nigra pars reticulata. A number of experiments are required to prove or disprove this hypothesis.